2018
DOI: 10.1136/archdischild-2018-315221
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of a scoring instrument for training and testing neonatal intubation skills

Abstract: ObjectiveTo determine the validity, reliability, feasibility and applicability of a neonatal intubation scoring instrument.DesignProspective observational study.SettingSimulation-based research and training centre (Center for Advanced Pediatric and Perinatal Education), California, USA.SubjectsForty clinicians qualified for neonatal intubation.InterventionsVideotaped elective intubations on a neonatal patient simulator were scored by two independent raters. One rater scored the intubations twice. We scored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Based on this study and its prequel, 19 it can be concluded that our NISI is valid, reliable, and practical. It can be used to assess (simulated) neonatal intubations in real time and remotely on video.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…Based on this study and its prequel, 19 it can be concluded that our NISI is valid, reliable, and practical. It can be used to assess (simulated) neonatal intubations in real time and remotely on video.…”
Section: Resultsmentioning
confidence: 65%
“…In the present study, we evaluated the construct validity and reliability of real-time assessment of our previously published NISI. 19 Using an extreme groups design, we found a significant positive correlation between intubation experience and performance. In addition, we demonstrated that structured, individualized feedback improved subsequent neonatal intubation performance.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations